THE ROLE OF PROVERBS IN MODERN LINGUISTICS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Proverbs have been a vivid reflection of people’s minds, observations, and attention to the environment, intellect, centuries of life experience, and way of life over the years and centuries. This artistic mirror reflected his attitude to life, nature, man, family and society, his socio-political, spiritual, moral-aesthetic and philosophical views, in short, himself and his identity.